Efficiency of castor oil–based polyurethane foams for oil sorption S10 and S500: Influence of porous size and statistical analysis - Alves, Fillip C [UNESP] (2021)
This study evaluates the efficiency of castor oil–based polyurethane foams for oil sorption S10 and S500, focusing on the influence of the pores’ size. Different foams were produced by varying the polyol: isocyanate ratio (1:0.3; 1:0.5; 1:1.0; 1:1.5; and 1:2.0). The physicochemical properties, morphology, density, and Hg porosity were determined. The sorption capacity was influenced by exposure time, oil viscosity, and concentration of the reagents, considering variations in the hydrophobicity, void content, and morphology. The results showed that the foam produced at an in the same mass proportion (PUC) has a higher sorption capacity in exposure time from 25 to 40 h due to higher void content and larger pore diameter size. It was observed that the lower viscosity of S10 diesel contributes to the higher sorption efficiency compared to S500 one. The Taguchi method corroborated the mentioned results, indicating a higher sorption trend by varying the reagent concentration and exposure times.